Polymorphisms of candidate genes for muscle performance and male fertility in Brazilian Mangalarga horses - Arneiro, Lidia Carolina Meira [UNESP]; Curi, Rogério Abdallah [UNESP]; Chardulo, Luis Artur Loyola [UNESP]; Puoli Filho, José Nicolau Prospero [UNESP]; Mota, Marcilio Dias Silveira da [UNESP] (ScopeMed, 2012)
The aims of the present study were to propose a polymerase chain reaction-restriction fragment length polymorphism PCR-RFLP genotyping method for the AY_376689:c.773C>T single nucleotide polymorphism SNP of the equine PRKAG3 gene, related to muscle performance, as well as to characterize this SNP and a second polymorphism, AAWR_02017454:g.121684T>C of the SPATA1 gene, related to male fertility, in Mangalarga horses, in order to provide a basis for future studies investigating the association between markers and traits of interest in this breed. For this, 151 Mangalarga horses of both sexes, representatives of the population of the Sate of São Paulo, Brazil, were used. Polymerase chain reaction-restriction fragment length polymorphism PCR-RFLP was found to be adequate for the genotyping of the AY_376689:c.773C>T single nucleotide polymorphism SNP of the PRKAG3 gene. However, this polymorphism probably does not segregate in Mangalarga horses, a fact impairing association studies with muscle performance traits. The estimates of population genetic parameters obtained for the AAWR_02017454:g.121684T>C polymorphism of the equine SPATA1 gene demonstrated the possibility of association studies between this marker and traits related to male fertility.
Keywords: Mangalarga horses; PRKAG3; SNP; SPATA1